2014
DOI: 10.1007/s13197-014-1330-x
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory and steady shear rheology of gellan/dextran blends

Abstract: Oscillatory and steady shear rheology of gellan (G) and dextran (D) solution individually, and in blends (G/D ratio 1:1, 1:2, and 1:3 w/v) with a total hydrocolloid concentration of 3 % (w/v) were studied at 25°C. Individually, 1.5 % dextran and 1.5 % gellan in solution exhibited Newtonian and non-Newtonian behavior, respectively. A blend of equal proportion of dextran and gellan (G/D=1:1) exhibits a distinct gel point (G′ = G″), and further addition of dextran in the blend (G/D=1:2 and 1:3) resulted predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…A good network structure can be formed by adding 0.25% gellan gum, which can reach the gel strength of 1% of κ‐carrageenan (Oliveira et al, ). When gellan gum was incorporated into chicken meat batters, it was hydrated or dissolved and formed a gel mixture with chicken myofibrillar proteins after heating, which contributed to reduce the loss of water from external addition and chicken batters (Ahmad, Ahmed, Hashim, Manap, & Mustafa, ; Dai, Liu, Liu, & Tong, ). Duda, Pietrasik, Cieslik, and Tubaj () reported that incorporation of gellan gum into sausages increased cooking yield and reduced thermal drip.…”
Section: Resultsmentioning
confidence: 99%
“…A good network structure can be formed by adding 0.25% gellan gum, which can reach the gel strength of 1% of κ‐carrageenan (Oliveira et al, ). When gellan gum was incorporated into chicken meat batters, it was hydrated or dissolved and formed a gel mixture with chicken myofibrillar proteins after heating, which contributed to reduce the loss of water from external addition and chicken batters (Ahmad, Ahmed, Hashim, Manap, & Mustafa, ; Dai, Liu, Liu, & Tong, ). Duda, Pietrasik, Cieslik, and Tubaj () reported that incorporation of gellan gum into sausages increased cooking yield and reduced thermal drip.…”
Section: Resultsmentioning
confidence: 99%
“…Previous groups that have characterized hydrogel precursor solutions have reported that experimental results respect the HB model. [59][60][61] For reporting hydrogel precursor properties, quantification of yield stress and shear response adequately provides information for comparison of materials within the hydrogel community.…”
Section: Herschel-bulkley Modelmentioning
confidence: 99%
“…a reduction provides advantages during high-shear processing operations, whereas an increase results in the desired mouthfeel during consumption. 18,22 The Herschel-Bulkley model was used to quantitatively describe flow curves in relation to starch type and concentration. The magnitudes of yield stress (τ 0 ), consistency index (k) and flow behavior index (n) for the ascending curves (20°C) are demonstrated in Table 1.…”
Section: Steady-state Shear Rheological Propertiesmentioning
confidence: 99%
“…The decrease in m 0 and m 00 values clearly indicates the liquid-semisolid transformation of BEGs, more noticeable in samples containing PS than WMS. 22,26 Quality factor (Q) was applied to unify K 0 , K 00 , m 0 , m 00 and the values determined at 10 Hz are presented in Table 2. Starch addition yielded higher magnitudes of Q (r ≥ 0.991, P < 0.001).…”
Section: Steady-state Shear Rheological Propertiesmentioning
confidence: 99%